Number of bite marks by animals on artificial fruits and insects after an exposure time of 96h on all focal plots of the Kilimanjaro Research Unit - Katrin Böhning-Gaese; Stefan W Ferger; Hamidi Iddi Dulle; Matthias Schleuning (PANGAEA, 2018)
We quantified frugivory and insectivory rates with artificial fruit and insect experiments on the focal plots of all 13 habitat types in the warm dry season (December to March) and in the cold dry season (July to October). We used non-toxic, odorless modeling clay (1) to mold spherical fruits of 14 mm diameter in three colors that have been associated with the avian seed dispersal syndrome: black, red and violet (Flörchinger et al. 2010) and (2) to mold green artificial caterpillars. We exposed the artificial fruits and caterpillars in ten clusters per focal plot with a minimum distance of 10 m between clusters. In each cluster, we placed 20 fruits per color or 20 caterpillars, respectively, resulting in a total number of 15,600 artificial fruits (13 habitat types x 10 clusters x 3 colors x 20 fruits per color and cluster x 2 seasons) and 5,200 artificial caterpillars (13 habitat types x 10 clusters x 20 caterpillars per cluster x 2 seasons). We used florist extquotesingles wire to attach the fruits and caterpillars to small twigs of bushes or trees in a height of about 12 m above ground with a minimum distance of 1 m between colors and 10 cm between fruits of one color. Artificial fruits and caterpillars were exposed for 96 h hours and then checked for peck or bite marks of birds, mammals and reptiles, which indicated that a potential disperser attempted to eat the artificial fruits or caterpillars, respectively.
Supplement to: Ferger, Stefan W; Dulle, Hamidi Iddi; Schleuning, Matthias; Böhning-Gaese, Katrin (2016): Frugivore diversity increases frugivory rates along a large elevational gradient. Oikos, 125(2), 245-253, https://doi.org/10.1111/oik.02296